KONTRAK ELEKTRONIK DALAM PERDAGANGAN INTERNASIONAL DITINJAU DARI PERSPEKTIF HUKUM POSITIF INDONESIA - Derry Angling Kesuma (GoAcademica Research dan Publishing, 2018)
The growth of international trade and trade as a result of technological developments in the last ten to fifteen years, which is commonly referred to as